PDZD8 interacts with Protrudin and Rab7 at ER-late endosome membrane contact sites associated with mitochondria - Elbaz-Alon, Yael; Guo, Yuting; Segev, Nadav; Harel, Michal; Quinnell, Daniel E.; Geiger, Tamar; Avinoam, Ori; Li, Dong; Nunnari, Jodi (Nature communications)
Endosomes are compositionally dynamic organelles that regulate signaling, nutrient status and organelle quality by specifying whether material entering the cells will be shuttled back to the cell surface or degraded by the lysosome. Recently, membrane contact sites (MCSs) between the endoplasmic reticulum (ER) and endosomes have emerged as important players in endosomal protein sorting, dynamics and motility. Here, we show that PDZD8, a Synaptotagmin-like Mitochondrial lipid-binding Proteins (SMP) domain-containing ER transmembrane protein, utilizes distinct domains to interact with Rab7-GTP and the ER transmembrane protein Protrudin and together these components localize to an ER-late endosome MCS. At these ER-late endosome MCSs, mitochondria are also recruited to form a three-way contact. Thus, our data indicate that PDZD8 is a shared component of two distinct MCSs and suggest a role for SMP-mediated lipid transport in the regulation of endosome function. Membrane contact sites between organelles have been shown to play important biological roles. Here, the authors show that at the ER, PDZD8 associates with Protrudin and also with Rab7 endosomes and recruits mitochondria to form three-way contacts.